Protocol for in vitro germination and micropropagation of Himatanthus Sucuuba (Spruce ex Müll. arg.) Woodson (Scientia Agropecuaria, 2025)
Himatanthus sucuuba is important in folk medicine and is widely used as an antitumor, antifungal, vermifuge and anti-anemic agent1. In this context, the objective of this study was to develop a protocol for in vitro germination and micropropagation of H. sucuuba. The seeds were immersed in a 1.0% (v/v) Cabrio Top solution for one hour on a magnetic stirrer and then in a 0.1% (v/v) diluted NaOCl solution for 30 minutes under agitation, followed by immersion in 70% alcohol for 1 minute. Subsequently, the seeds were rinsed four times with sterile distilled water and then inoculated in MS medium supplemented with the auxins AIA, ANA and AIB at concentrations of 0.0; 1.0; 3.0; 5.0 mg L-1. The experimental design was completely randomized, using 10 treatments with 3 replicates of 10 seeds (n = 30). It was observed that the MS medium supplemented with IAA (5.0 mg L-1) resulted in 80% germination and seedlings with 5.97 cm in height and 4.2 nodal segments. To stimulate rooting, the nodal segments were cut and inoculated in MS medium supplemented with BAP (0.1 mg L-1) and in interaction with the auxins IAA, 2,4-D and ANA, at concentrations of 0.0; 3.0; 5.0 and 8.0 mg L-1 and kept in a growth room at 25 ± 2 °C, with a photoperiod of 16 h. The combination BAP+IAA (0.1 + 8.0 mg L-1) showed the best results with 100% sprouting, 40% callus formation and 30% rooting. In conclusion, in vitro propagation is a promising technique to produce H. sucuuba seedlings, however, hormonal adjustments are necessary.
Keywords: Tissue culture; growth regulators; in vitro rooting; medicinal species; sucuuba